Novel botanical active component derivatives containing carboxamide and 1,3,4-Thiadiazole thioether moieties: Design, synthesis, and inhibitory activity - Li, Pei; Chen, Cong; Zhu, Rongxi; Yang, Guixia; Xu, Min; Wan, Guanghua; Wang, Xiang (Frontiers in Chemistry, 2022)
In this study, using the botanical active components of carvacrol, thymol, guaiacol, and sesamol as the lead structures, 19 novel botanical active component derivatives containing carboxamide and 1,3,4-thiadiazole thioether moieties (5a−5s) were synthesized and structurally characterized by 1H NMR, 13C NMR, and HRMS. The antibacterial bioassay results in vitro showed that compound 2-(2-methoxyphenoxy)-N-(5-(methylthio)-1,3,4-thiadiazol-2-yl)acetamide (5k) revealed excellent inhibitory activities against Xanthomonas axonopodis pv. citri (Xac) and Xanthomonas oryzae pv. oryzicolaby (Xoc), the median effective concentration (EC50) values of 22 and 15 μg/mL, respectively, which were even better than those of thiodiazole copper and bismerthiazol. Meanwhile, all the target compounds revealed lower in vitro inhibitory effects on Mucor bainieri (M. bainieri), Mucor fragilis (M. fragilis), and Trichoderma atroviride (T. atroviride), than carbendazim.